Behaviour of titanium dioxide and zinc oxide nanoparticles in the presence of wastewater-derived organic matter and implications for algal toxicity. Issue 1 (1st December 2014) - Neale, Peta A.; Jämting, Åsa K.; O'Malley, Elissa; Herrmann, Jan; Escher, Beate I.
Abstract : This study compared the behaviour and effect of TiO2 and ZnO nanomaterials in wastewater effluent, humic acid and test media. Abstract : The properties of engineered nanomaterials (ENMs), such as their small size and increased reactivity, enable their use in a wide range of products; however, these attributes may also pose an environmental hazard. Wastewater effluent is expected to be a significant source of ENMs to the aquatic environment. Little is known about the behaviour and effect of ENMs in this complex matrix. The aim of this study was to assess the effect of titanium dioxide (TiO2 ) and zinc oxide (ZnO) ENMs on microalgae Pseudokirchneriella subcapitata in wastewater effluent and compare with more commonly tested matrices, specifically Talaquil growth media and Suwannee River humic acid. To better understand the toxicity results, ENM concentration, size and streaming potential in the different experimental matrices were assessed. The different media types had a significant influence on TiO2 behaviour, with TiO2 settling out of solution within the first 24 hours in wastewater. However, as TiO2 was not toxic to algae at the studied concentration, no difference in effect was observed between media, humic acid and wastewater. In contrast, media types had less of an influence on ZnO behaviour, with growth inhibition observed in all three media types at 72 hours, although the presence of organic matter delayed inhibition slightly. The results demonstrate that organic matter properties can have a significant influence on ENM behaviour, and while this did not translate into an effect on algae in the current study, it is still important to consider ENM behaviour and fate when working in different matrices.